Principles and practice of sex therapy - Hall, Kathryn S. K.; Binik, Yitzchak M. (New York : The Guilford Press, 2020)
"This widely used clinical reference and text--now significantly updated with 75% new material reflecting therapeutic advances, diagnostic changes, and increased coverage of sexual minority groups--comprehensively addresses sexual problems and their treatment. Prominent contributors interweave theory, research, and clinical considerations. Detailed case examples illustrate the process of assessment and intervention with individuals and couples across the lifespan, with attention to gender-related, cultural, and health concerns. The volume features an integrative introduction and conclusion, plus an instructive editorial commentary at the beginning of each chapter"--
Includes bibliographical references and index.
Keywords: Sexualitet; Terapimetoder; Sex therapy; Sex therapy; Sex; Sex Customs; Therapeutics